P14.108 Bevacizumab versus alkylating chemotherapy in recurrent glioblastoma. (6th September 2019) - Seystahl, K; Hentschel, B; Loew, S; Gramatzki, D; Felsberg, J; Herrlinger, U; Westphal, M; Schackert, G; Thon, N; Schlegel, U; Tatagiba, M; Pietsch, T; et al.
Abstract: BACKGROUND: The use of alkylating chemotherapy versus bevacizumab for recurrent glioblastoma remains controversial. Here we tested the hypothesis that the activity of alkylators, but not that of bevacizumab, would be associated with the O 6 -methylguanine DNA methyltransferase ( MGMT ) promoter methylation status PATIENTS AND METHODS: We analyzed a cohort of patients treated at centers of the German Glioma Network or the University Hospital Zurich with alkylating agent-based chemotherapy (n=260) or bevacizumab without or with irinotecan (n=84) for first recurrence of glioblastoma. Outcome was stratified for MGMT status and cross-over to bevacizumab or alkylators at further tumor progression. RESULTS: Median post-recurrence survival-1 (PRS-1) for patients receiving alkylating agent chemotherapy at first recurrence was longer than for patients receiving bevacizumab (11.1 versus 7.4 months, p<0.001). The use of alkylating agents was associated with longer PRS-1 for patients with a methylated versus an unmethylated MGMT promoter (p=0.017). For patients receiving bevacizumab, PRS-1 was not different with or without MGMT promoter methylation. PRS-1 was longer in the group receiving alkylating chemotherapy compared to bevacizumab for patients with a methylated (p<0.001) or unmethylated MGMT promoter (p=0.034). For patients with alkylators at first recurrence receiving bevacizumab at any further recurrence, PRS-1 was longer than in patients receiving bevacizumab first and alkylators thereafter (p=0.002). CONCLUSION: This study confirms limited value of bevacizumab in recurrent glioblastoma independent of MGMT status. Alkylating agents have activity in recurrent glioblastoma, especially in the context of a methylated MGMT promoter.